Acute Muscle Injuries - Kerkhoffs, Gino M.M.J; Servien, Elvire (Springer International Publishing : Imprint: Springer, 2014)
Sports participation at both amateur and professional levels has increased enormously in recent decades, impacting positively on all aspects of health except musculoskeletal injuries. Acute muscle injuries account for approximately 20% of all injuries in sports and pose an increasing challenge for athletes and medical practitioners. This book documents current knowledge and standards of care for acute muscle injuries. The full range of injuries is covered, including those to the hamstring, hip adductor, quadriceps, calf, pectoralis major, biceps brachii, latissimus dorsi, and rectus abdominis muscles. Evidence-based content is combined with experience from medical experts from around the globe in order to provide the reader with a full picture of the latest insights into terminology, trauma mechanisms, basic principles of healing, diagnosis, and treatment. Helpful diagnostic and treatment algorithms are included, and clear guidance provided on ensuring optimal rehabilitation and rapid return to sports. Acute Muscle Injuries is structured in such a way that it will serve as an ideal reference manual for orthopaedic surgeons, sports medicine physicians, physiotherapists, general practitioners, paramedics, sports managers, athletes, and coaches. The authors are all scientifically active in the field of sports medicine and also well known for their great clinical experience in the care of acute muscle injuries.